Crown Characteristics and Bole Attributes in a Chronosequence of tectona Grandis Linn. F. Young Stands in the Moist Deciduous Forests of Northern India - Jha, Kaushalendra Kumar (Indian Forester, 2008)
In recent years Teak has become a prominent short rotation plantation crop in many tropical countries both within and outside its natural range. Although stand structure, crown attributes and stand productivity are interrelated, data on crown structure and related parameters of teak are scarce. Therefore, a study on chronosequence young plantations aimed at establishing relationships among them. The plantations aged 1, 5, 11, 18, 24 and 30 year were selected in the moist deciduous region of North India where teak was introduced as a viable crop. Sixty four trees, three each in all diameter classes of all stands except where trees were occasionally not available in requisite number for a certain diameter class, were harvested to measure crown and bole dimensions. Forty regression equations using MS-Excel were developed linking crown and bole parameters with age. Most of the equations providing cue to further research or management strategy were found statistically significant. With the help of crown and bole measurements tree silhouettes have been created as two-dimensional figures using Coral Draw 10 to have comparative shape and size of bole and crown at different age in young life of teak. The boles were cylindro-conical while crowns varied from cylindro-elliptical in younger stands to elliptico-parabolloid in older stands. The equations developed in this study provide a means for predicting the variables dependent on crown since they showed strong correlation between crown and other tree parameters. With the help of these equations crown features available from aerial photograph data can be converted into growing stock in terms of density or biomass or volume. Such growing stock assessment will be helpful in crop management decisions. In addition to above basic inventory data like bole diameter may generate crown features. Thus the predicted values can be used as ground truthing in aerial photography interpretation without going through extremely cumbersome direct crown measurement process.